SCRUTINIZING PICTURES, ESSENTIALIZING ECOLOGICAL CARE: ANALYSIS OF ECOLOGICAL LINGUISTIC LANDSCAPE ON ENVIRONMENTAL EDUCATION POSTERS IN SCHOOLS - Eti Setiawati; Sony Sukmawan; Dany Ardian; Fredy Nugroho Setiawan; Elisabeth Worobroto Purwaningrum (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
Ecologically oriented poster texts contain ecological information and messages. These texts can be categorized as ecocritical text. Environmental (care) posters, in particular, can be found in schools. This is due to regulatory reasons, school reputation, and school initiative. Environmental posters are potential media for character education which concerns with environmental care. In order to find the socio-ecological meaning of the poster texts in internal public spaces (schools) and use them as a stepping stone to strengthen the nation’s character, an integrated linguistic landscape and ecocriticism approach is used. The results show ecocritical posters in schools visually depict ideal places and harmonious conditions. In terms of ideas, the ecocritical posters have presented natural environment (non-human) as an existence that determines the survival of humans; therefore, humans and non-humans interests are legitimate respectively. Furthermore, the existing condition of the environment is communicated through a symbolic vision of damage and destruction.